Blockchain, Wikis, and the Ideal Science Machine: With an Example From Genomics - Koepsell, David (Frontiers in Blockchain, 2019)
Until now we have lacked a technology that could well capture the processes of science in a way that preserves every step, and creates a full audit trail. Combining wiki technologies and blockchain provides us with a new opportunity: to create a “science machine” that folds all processes together, from instrument to publication, and enabling science to proceed as never before with greater transparency, accountability, and reproducibility. Here I discuss the theory and method that might be combined to create such a science machine with special reference to the nature of genomic science.